ACTING-OUT BEHAVIOR" PADA ANAK: ANALISIS KASUS DI KELAS 4A AKIBAT PERSAINGAN SAUDARA - Susanto, Eri (Al Banin : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study analyzes the manifestation of acting-out behavior (acting-out behavior) experienced by a 10-year-old male student in Grade 4A of SDN Pondok Cabe Ilir 01. Deviant behaviors such as delinquency, bullying friends, theft, and decreased academic achievement were identified as a response to sibling rivalry and lack of parental attention. Case analysis indicates that the main contributing factor is parental attention deficit due to being busy taking care of a toddler and earning a living. The situation is exacerbated by the grandmother's permissive parenting style and negative influences from the social environment. This case highlights that the student experienced a lack of emotional support and inconsistent parenting styles, which significantly contributed to the expression of his negative behaviors. Therefore, this study recommends a comprehensive intervention that focuses on restoring quality parental attention, aligning grandmother's parenting style with positive discipline, as well as providing guidance and counseling support and developing social skills at school. The success of the intervention depends heavily on consistency and close collaboration between the family and the school. This research is expected to provide insight for educators and parents in dealing with acting-out behavior in children related to family dynamics